Laboratory tests of bentonite stabilization of bottom sediments from a dam reservoir in relation to their usage in municipal solid waste landfill liners - Karolina Koś; Eugeniusz Zawisza (Acta Scientiarum Polonorum. Formatio Circumiectus)
Geotechnical parameters of bottom sediments from a dam reservoir (Rzeszowski Reservoir, Poland) with bentonite addition are presented in the paper. Tests were carried out in the aspect of the possible usage of sediments as a material for soil liners in Municipal Solid Waste Landfill. Mentioned sediments did not fulfilled the permeability and plasticity criteria defined for soils that can be used in liners. The bentonite addition caused, among other things, a decrease in permeability coefficient and increase in plasticity index. Based on the carried out tests it was stated that sediments with 6% addition of bentonite fulfil all requirements and can be used for liners in MSWL.